Effect of glycyrrhizic acid on the oral absorption of paeoniflorin in rats in vivo. Issue 52 (12th May 2016) - Sun, Yuming; Yang, Yang; Li, Xiaohui; Chang, Mingming; Li, Dong; Pu, Tingting; Ding, Xue; Wang, Qing; Wang, Yulin
Abstract : The effect of glycyrrhizic acid (GL) on the absorption of paeoniflorin (PF) was GL dosage dependent in rats. The C max of PF decreased significantly when GL at the dosage of 300 mg kg −1 BW, while it increased with the increase of the dosage of GL. Abstract : Paeoniflorin (PF) and glycyrrhizic acid (GL) are the major active components in the peony liquorice decoction, which has been widely used clinically in China for more than one thousand years. The available reports on the pharmacokinetic behaviour of the two compounds in the presence of each other still are not consistent and are sometimes even contradictory. The aim of this study was to investigate the effect of GL on the absorption of PF administrated orally with or without pre- or co-administration of GL at different dosages in rats. The results indicated that GL has effects on the absorption extent of PF, however, without any significant impact on the absorption rate and excretion of PF. Furthermore, the effect of GL on the absorption of PF was GL dosage dependent and the concentration of GL in the small intestinal tissue should be a decisive factor for the effect. GL (300 or 900 mg kg −1 BW) showed an inhibition effect on the absorption of PF (300 mg kg −1 BW) when the two drugs were co-administrated orally, while the effect was reversed when GL at a higher dosage of 2700 mg kg −1 BW. The present study explained the contradiction of varying reports on the effect of GL on the absorption of PF and will provide important information for the rational design of peony and liquorice based formula in TCM.